Anthropometric profiles of children with congenital heart disease (Faculty of Medicine Universitas Indonesia, 2011)
Background: Undernutrition is a common cause of morbidity in children with CHD. Previous data from developing country showed prevalence of preoperative undernutrition in children with CHD was up to 45%. The aim of this study are to determine the anthropometric profiles and prevalence of undernutrition in children with CHD by using the anthropometric measurement. Methods: A cross-sectional study was carried out in children aged 0-2 years old with CHD in Cipto Mangunkusumo hospital. All patients underwent an anthropometric evaluation (weight, length and head circumference) at presentation. Undernutrition, failure to thrive /FTT, short stature and microcephaly were determined according to WHO, weight-for-length, weight-for-age at 2 points, length-for-age, head circumference-for-age z-score < -2SD accordingly. Results: We had total of 95 patients, 73 patients with acyanotic and 22 patients with cyanotic lesions. Prevalence of undernutrition in CHD was 51.1%, with 22.3% severe undernutrition. FTT was found in 64.9%, short stature in 49.5% and microcephaly in 37% patients. FTT was found higher in acyanotic (72.2%) compared to cyanotic lesions (42.9%). In acyanotic, weight was affected more than length (72.2% vs 49.3%). In cyanotic, weight and length affected equally (42.9% vs 54.5%). Diet counseling were done in patients with undernutrition. Medicines, transcatheter or surgery intervention were indicated in selected patients. Conclusions: Prevalence of FTT was higher than undernutrition in children with CHD. FTT was found higher in acyanotic lesions. In acyanotic, weight was affected more than length. In cyanotic, weight and length affected equally. (Med J Indones 2011; 20:40-5) Keywords: congenital heart disease, failure to thrive, short stature, undernutrition